Literature Review: The Effect of Audit Delay, Management Changes, and Audit Opinion on Auditor Switching - Suryanta, Aris; Kuntadi, Cris (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This article examines and reviews the determinants of auditor switching, namely: audit delay, management changes, and audit opinion on a study of audit literature. The objective of this article was to determine the hypothesis of the influence between variables that can be used in further studies. The methods of this article were descriptive qualitative and library research. The results of this literature review article indicated that (1) audit delay has a positive impact on auditor switching; (2) management changes have a positive impact on auditor switching; and (3) audit opinion has a positive effect on auditor switching. These results add to the study of literacy related to the factors causing auditor switching.